Healthy ageing at work: efficacy of group interventions on the mental health of nurses aged 45 and older : results of a randomised, controlled trial - Maatouk, Imad; Nikendei, Christoph; Herbst, Kirsten; Herzog, Wolfgang (PLOS ONE, 2018)
Objective This multicentre, randomised controlled trial (RCT) aimed to evaluate the efficacy of a small-group intervention promoting successful ageing at work in older nurses (aged ≥45). Method A sample of 115 nurses aged ≥45 from 4 trial sites in Germany were randomly assigned to either the intervention group (IG), that received a small-group intervention of seven weekly sessions of 120 min with a booster session after six weeks or to a wait-list control condition (WLC). Outcomes were measured via validated self-report questionnaires at baseline (T1) and at post-treatment (T2). Primary outcomes were mental health-related well-being and mental health-related quality of life (QOL). The secondary outcomes included mental health-related and work-related measures. Results The intention to treat (ITT) analysis showed significant positive effects of the intervention on mental health. A significant small effect (d = 0.3) in favour of the IG was found for psychological health-related quality of life. Positive small effects (d = 0.24 to d = 0.31) were also found for work related mental strain. Conclusions Our small-group intervention based on a theory of successful ageing for nurses aged ≥45 was found to be effective with regard to improvements of psychological health related quality of life and other mental health-related outcomes. Thus, our study shows that the ageing workforce can be reached through specifically designed preventive interventions. The components of our intervention could be easily adapted to the belongings of other professions. Our results suggest that these components should be evaluated in various settings outside the healthcare sector.